Increasing bioelectricity generation in microbial fuel cells by a high-performance cellulose-based membrane electrode assembly. (15th January 2021) - Mashkour, Mehrdad; Rahimnejad, Mostafa; Mashkour, Mahdi; Soavi, Francesca
Highlights: Fast, easy and cheap fabricating cellulose-based membrane electrode assembly (MEA) The much lower resistance of the MEA than commercial gas diffusion electrode (GDE) Improving apparent capacitance of microbial fuel cell (MFC) by the use of the MEA. Almost double the pulse power density of MFC by the cellulosic MEA (1790 mW m −2 ) Up to 250% of columbic efficiency improvement by using the MEA compared to GDE. Abstract: Economically harvesting energy from a microbial fuel cell (MFC), increasing its electrical power production, and developing its role as a practical energy supply, needs a low-cost and high-performance design of the MFC compartments. According to this strategy, a novel monolithic membrane electrode assembly (MEA) was fabricated and evaluated as an air–cathode in a single-chamber MFC (SCMFC). The MEA was made of bacterial cellulose (BC), conductive multi-walled carbon nanotubes (CNT), and nano-zycosil (NZ). BC, as a nano-celluloses with oxygen barrier property, can maintain anaerobic conditions for the anode compartment. Binder-less CNT coating on BC avoids costly binders such as poly-tetra fluoro ethylene (PTFE) and Nafion and decreases the MEA charge transfer resistance. NZ, as a very cheap modifier, not only prevents the anolyte leakage but also provides more MEA's active sites for the oxygen reduction reaction (ORR). The electrochemical performance of the MEA was compared to a PTFE- based gas diffusion electrode (GDE) in the SCMFC. The MEA cell provided a pulse power density of 1790 mW/m 2, roughly twice as high as the pulse power density of GDE (920 mW/m 2 ). SCMFC's internal resistance decreased from 1.84 KΩ (with GDE) to 0.8 KΩ (with MEA). Also, the cell's columbic efficiency increased from 4.2% (with GDE) to11.7% (with MEA). Additionally, the capacitance of the MEA (65 mF) was much higher than the value for GDE (0.73 mF). Thus, the MEA compared to the GDE showed higher performance in the SCMFC for electricity generation and wastewater treatment at a lower cost.